2017
DOI: 10.22146/jpsi.18377
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Full or Empty Inside? Peran Perbedaan Individual dalam Struktur Pengalaman Afektif

Abstract: Abstract. Literatures on alexithymia and rumination are typically separated; however, the negative manifestations of both traits can potentially be attenuated by trait self-control. This experiment (N = 85) aimed to explore the dynamics of self-reported alexythimia, rumination, and self-control toward an individual's structure of current affect. Participants were asked to rate affective valence and arousal of 60 stimuli from the International Affective Picture System (IAPS) using Self-Assessment Manikin (SAM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Compared to another self-control questionnaire, SCS shows a stable relationship with various behaviors that require self-control (De Ridder et al, 2012). Brief SCS reliability score for undergraduate samples in Indonesia was α = .75 (Yusainy, 2017).…”
Section: Instrumentsmentioning
confidence: 99%
“…Compared to another self-control questionnaire, SCS shows a stable relationship with various behaviors that require self-control (De Ridder et al, 2012). Brief SCS reliability score for undergraduate samples in Indonesia was α = .75 (Yusainy, 2017).…”
Section: Instrumentsmentioning
confidence: 99%
“…and reflection (Analyze recent events to try to understand why you are depressed). In the study of Treynor et al (2003), the internal consistency of this measuring instrument is in the good category with Cronbach's alpha .85, In addition, in a study conducted by Yusainy (2017) it is known that this measuring instrument has internal consistency with Cronbach's alpha .74. The results of reliability tests conducted in this study showed Cronbach's alpha obtained was .75.…”
Section: Measurementmentioning
confidence: 99%
“…TAS-20 merupakan alat ukur terbaik untuk mengukur alexithymia dengan validitas dan reliabilitas yang baik. Dalam penelitiannya, Al Yusainy menggunakan validitas konstruk TAS-20 yang telah didukung oleh hasil penelitian yang menunjukkan bahwa alat ukur tersebut memiliki struktur factorial yang konsisten dengan tiga dimensi alexithymia yang diusulkan (Yusainy, 2017). Kemudian untuk mengukur tingkat depresi, peneliti menggunakan Beck Depression Inventory-II (BDI-II) yang sudah ditranslasi oleh Ginting.…”
Section: Pengukuranunclassified